Autologous meniscus fragments embedded in atelocollagen gel enhance meniscus repair in a rabbit model - Norimasa Matsubara; Tomoyuki Nakasa; Masakazu Ishikawa; Takayuki Tamura; Nobuo Adachi (Bone & Joint Research, 2021)
Aims: Meniscal injuries are common and often induce knee pain requiring surgical intervention. To develop effective strategies for meniscus regeneration, we hypothesized that a minced meniscus embedded in an atelocollagen gel, a firm gel-like material, may enhance meniscus regeneration through cell migration and proliferation in the gel. Hence, the objective of this study was to investigate cell migration and proliferation in atelocollagen gels seeded with autologous meniscus fragments in vitro and examine the therapeutic potential of this combination in an in vivo rabbit model of massive meniscus defect. Methods: A total of 34 Japanese white rabbits (divided into defect and atelocollagen groups) were used to produce the massive meniscus defect model through a medial patellar approach. Cell migration and proliferation were evaluated using immunohistochemistry. Furthermore, histological evaluation of the sections was performed, and a modified Pauli’s scoring system was used for the quantitative evaluation of the regenerated meniscus. Results: In vitro immunohistochemistry revealed that the meniscus cells migrated from the minced meniscus and proliferated in the gel. Furthermore, histological analysis suggested that the minced meniscus embedded in the atelocollagen gel produced tissue resembling the native meniscus in vivo. The minced meniscus group also had a higher Pauli’s score compared to the defect and atelocollagen groups. Conclusion: Our data show that cells in minced meniscus can proliferate, and that implantation of the minced meniscus within atelocollagen induces meniscus regeneration, thus suggesting a novel therapeutic alternative for meniscus tears.